Financial Sustainability of Nongovernmental Organizations in Nepal: A Qualitative Study (Tri-Chandra Journal of Anthropology, 2024)
This paper explores the financial sustainability of Nepalese NGOs, drawing insights from the resource dependency theory. The primary data were collected from the key informant interviews (N=15) with executives of development NGOs. The data were analyzed thematically based on Braun and Clarke’s (2006) framework using NVivo software. The findings showed that internal funding sources could not support NGOs financially. They were found to have suffered from resource constraints due to a decline in external funding opportunities. NGOs also appeared weak in adopting strategies necessary to maintain financial sustainability. The findings indicated the possibility of further resource constraints if the government and NGOs do not consider diversifying funding sources. Future studies should explore the internal financial management strategies of NGOs for maintaining their financial sustainability by employing case studies.